Camusian Rebellion and the Ethical Limits of Posthumanism - Sidabutar, Chrisoneiro Yoshua (Jurnal Filsafat "WISDOM", 2025)
This article examines how Albert Camus’s concepts of absurdity and rebellion can serve as an ethical framework in responding to posthumanist ideologies that challenge human subjectivity and autonomy. The research objective is to critically analyze the relevance of Camus’s existential philosophy in addressing the ethical dilemmas posed by posthumanism, particularly regarding technological transcendence and the erosion of human finitude. Adopting a normative-philosophical approach with textual analysis, the study investigates whether Camus’s notion of authentic rebellion offers a critical stance against posthumanist aspirations. The findings reveal that Camus’s idea of rebellion, grounded in justice, limits, and dignity, provides a strong ethical response to the dehumanizing effects of posthumanism. The study concludes that Camusian ethics affirms human responsibility and offers resistance to metaphysical escapism in hyper-technological contexts.